EKSPRESI KEAGAMAAN, DAN NARASI IDENTITAS: STUDI PROGRAM PESANTREN TAHFIDZ INTENSIF DAARUL QURAN CIPONDOH TANGERANG - Habibi Zaman Riawan Ahmad (Harmoni, 2014)
This article investigates the interaction between religious expression and identity. The discourse of religious expression and identity is revealed from in the relational process of identity formation. In this case, religious express displays a variety of patterns, indicated by both individual expression and communal expression in performing the rituals of recitation, prayer, and doing charitable work. Those three essential elements become parts of a whole that cannot be separated from religion. These forms of religious expression, both in regards to the individual and with society, is described as a narrative. This anthropological, narrative study uses an ethnographic approach, and takes the Intensive Tahfidz Program of Daarul Quran Boarding Schools, Cipondoh Tangerang as a case study.